2013
DOI: 10.1021/cn400172n
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Mu Opioids Differentially Regulate Thrombospondins 1 and 2 Isoforms in Astrocytes

Abstract: Chronic opioids induce synaptic plasticity, a major neuronal adaptation. Astrocyte activation in synaptogenesis may play a critical role in opioid tolerance, withdrawal, and dependence. Thrombospondins 1 and 2 (TSP1/2) are astrocyte-secreted matricellular glycoproteins that promote neurite outgrowth as well as dendritic spine and synapse formation, all of which are inhibited by chronic μ opioids. In prior studies, we discovered that the mechanism of TSP1 regulation by μ opioids in astrocytes involves crosstalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…In this study, we investigated the mechanisms mediating the induction of OIH and the prolongation of PGE 2 -induced hyperalgesia in Type II hyperalgesic priming. In particular, we examined the role of the interaction of MOR, a Gα i -protein coupled receptor (GPCR) with epidermal growth factor receptor (EGFR), a receptor tyrosine kinase (RTK) that has been demonstrated to have crosstalk with opioid receptors [10; 16; 42]. We also investigated second messenger, downstream of MOR, involved in the induction of OIH and prolongation of PGE 2 hyperalgesia in Type II hyperalgesic priming.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the mechanisms mediating the induction of OIH and the prolongation of PGE 2 -induced hyperalgesia in Type II hyperalgesic priming. In particular, we examined the role of the interaction of MOR, a Gα i -protein coupled receptor (GPCR) with epidermal growth factor receptor (EGFR), a receptor tyrosine kinase (RTK) that has been demonstrated to have crosstalk with opioid receptors [10; 16; 42]. We also investigated second messenger, downstream of MOR, involved in the induction of OIH and prolongation of PGE 2 hyperalgesia in Type II hyperalgesic priming.…”
Section: Introductionmentioning
confidence: 99%
“…Glia cells have been shown to be able to be activated in neuropathic conditions, and the activated glia cells may release reactive factors to promote synaptogenesis in the developed nervous system. Then, the reactive synaptogenesis may result in various nervous system diseases [ 15 , 20 , 21 ]. Lo[ 41 ] found that, after neonatal unilateral transection of the infraorbital branch of the trigeminal nerve, glia cells were activated, demonstrated by cell proliferation and upregulation of GFAP, and accompanied by reactive synaptogenesis in the nerve projection zone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clearly further studies are needed to explore the synaptogenic roles of different increased TSPs after injury. It was also worthy to note that the microglia cells are also the source of TSP2[ 20 ]. The relatively small percentage of microglia cells is approximately 4% in retinal cell cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations